The memorial genre in academic context: formation memorials and academic memorials in comparison - Netto, Mônica Inês de Castro; Silva, Fátima (Linha D'Água, 2023)
The main objective of this paper is an analysis of memorials produced in academic context in terms of three variables: production conditions, text plan and discourse markers. The corpus is constituted by 30 memorials, 15 from students of two specialization courses and 15 from candidates for public examination for teaching career in varied areas of knowledge. The methodology of analysis has a mixed character and presents the following steps: a) analysis of production conditions and b) analysis of the text plan of each type of memorials; c) analysis of the most frequent discourse markers in each type of memorials; d) comparison of the two groups of memorials in relation to the analysis variables; e) discussion of the results. The results show differences in terms of the text plan and the connection marked using discourse markers in the two groups of memorials.